Lack of HLA class II antigen expression in microsatellite unstable colorectal carcinomas is caused by mutations in HLA class II regulatory genes - Michel, Sara; Linnebacher, Michael; Alcaniz, Joshua; Voss, Maike; Wagner, Rudolf; Dippold, Wolfgang; Knebel Doeberitz, Christina von; Knebel Doeberitz, Magnus von; Ferrone, Soldano; Kloor, Matthias (International journal of cancer, 2010)
Colorectal cancers (CRCs) develop on the basis of a deficient DNA mismatch repair (MMR) system in about 15% of cases. MMR-deficient CRC lesions show high-level microsatellite instability (MSI-H) and accumulate numerous mutations located at coding microsatellite loci that lead to the generation of immunogenic neopeptides. Consequently, the host's antitumoral immune response is of high importance for the course of the disease in MSI-H CRC patients. Accordingly, immune evasion mediated by impairment of HLA class I antigen presentation is frequently observed in these cancers. In this study, we aimed at a systematic analysis of alterations affecting HLA class II antigen expression in MSI-H CRC. HLA class II antigens are expressed by only two-thirds of MSI-H CRCs. The mechanisms underlying the lack of HLA class II antigens in a subset of MSI-H CRCs remain unknown. We here screened HLA class II regulatory genes for the presence of coding microsatellites and identified mutations of the essential regulator genes RFX5 in 9 (26.9%) out of 34 and CIITA in 1 (2.9%) out of 34 MSI-H CRCs. RFX5 mutations were related to lack of or faint HLA class II antigen expression (p = 0.006, Fisher's exact test). Transfection with wild-type RFX5 was sufficient to restore interferon gamma-inducible HLA class II antigen expression in the RFX5-mutant cell line HDC108. We conclude that somatic mutations of the RFX5 gene represent a novel mechanism of loss of HLA class II antigen expression in tumor cells, potentially contributing to immune evasion in MSI-H CRCs.